Ophthalmological knowledge of Family Health Network physicians working as first care providers in Brazil - Chaves, Igor Leonardo Carmona [UNESP]; Padovani, Carlos Roberto [UNESP]; de Cássia Moreira Zornoff, Denise [UNESP]; Ferreira, Ana Silvia Sartori Barraviera Seabra [UNESP]; Jorge, Edson Nacib [UNESP]; Schellini, Silvana Artioli [UNESP] (FapUNIFESP (SciELO), 2021)
OBJECTIVE: First care providers working in the Brazilian Unified Health System are often physicians from the Family Health Program. Their knowledge on ophthalmology could indicate whether there is a need for training to decrease ophthalmological demands to secondary or tertiary health levels. METHODS: A cross-sectional observational study based on an electronic questionnaire was conducted to evaluate the ophthalmological knowledge of Family Health Program physicians working at the VI Regional Health Department, Sao Paulo, Brazil. All Family Health Program physicians from this regional health department were invited, and the study included those who responded to the full questionnaire (115 physicians). The data were evaluated using descriptive analysis. RESULTS: There was no difference in the ophthalmological knowledge between sexes or in relation to undergraduate schools. Only 20% of the interviewees were specialized in Family and Community Medicine, which did not influence the number of correct answers. Only 22 (19.1%) physicians reported having enough knowledge about the main eye disorders, and 82 (71.3%) physicians considered themselves capable of treating ophthalmological emergencies. However, acute glaucoma was recognized by only 51 (44.3%) physicians, and eye perforations could only be handled by 65 (56.5%) of them. In addition, only 47 (40.9%) participants correctly answered that congenital cataracts should be operated right after diagnosis. CONCLUSIONS: Family Health Program physicians working as first care providers in the Health System in Brazil presented poor ophthalmological knowledge. Providing training on ophthalmology may improve the ophthalmological care at the primary level within SUS and reduce the case demands at other healthcare levels.
Keywords: Family health strategy; Health personnel; Ophthalmology; Regional health strategies; Unified health system